Speech acts: natural or normative kinds? - Ball, B (Wiley, 2014)
There are two views of the essences of speech acts: according to one view, they are natural kinds; according to the other, they are what I call normative kinds — kinds in the (possibly non-reductive) definition of which some normative term occurs. In this article I show that speech acts can be normative but also natural kinds by deriving Williamson’s account of assertion, on which it is an act individuated, and constitutively governed, by a norm (the knowledge rule), from a consideration of the natural characteristics of normal cases of its performance.